SCHOOL ENVIRONMENT AND ITS INFLUENCE ON EDUCATION OF CHILDREN WITH LEARNING DISABILITIES IN AWKA SOUTH L.G.A - Edwin-Ezeoka, Cynthia A.; Obidike, Ngozi D. (Journal of Early Childhood and Primary Education, 2020)
This study dwells on school environment and its influence on education of children with learning disabilities in Awka South L.G.A. The study adopted a survey design and was guided by two research questions. The population of the study comprise of 665 public primary school teachers among the 45 public primary schools in Awka South L.G.A. The study adopted simple random sampling for this study.  The researchers used balloting without replacement to select 15 public primary schools in Awka South L.G.A. Among these selected schools, the researchers selected 8 teachers from each of the selected schools giving a total of 120 primary school teachers. The instrument for the study was questionnaire drafted by the researchers with 24 items and titled School Environment and its Influence on Education of Children with Learning Disability (SEIECLD). The instrument was validated by three experts and later subjected to test on 15 primary school teachers in Awka North. Cronbach Alpha was used to compute score on this and a reliability value of 0.72 proved the reliability of the instrument. Mean was used to analyze the data collected. Findings from the study reveals among others that the school environment really has an influence on the education of the learning disabled child. Non availability of meaningful toys, and books coupled with location of the school and overgrown bushes, lack of functional ICT laboratory and other instructional materials such as insufficient whiteboards and play gadgets where challenges that influenced the education of the learning disabled child. Based on these findings, it was recommended among others that both governmental and non-governmental agencies should also ensure that basic schools are stocked with needed educational materials needed for the academic needs of children with learning disabilities.
Keywords: School environment; influence; education; learning disabilities